From Silence to Strength: Representation of Panchamar Women in Northern Sri Lankan Writings - Pavithira, K.; Thiruvarangan, M. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study examines the representation of Panchamar women in Northern Sri Lankan literature, focusing on the intersections of caste and gender oppression. Panchamar women are marginalized at various levels; these include caste-based exclusion, economic hardship and patriarchal constraints. Literature serves as a key place to record these experiences and as a medium for expressing women’s resistance to social institutions. The study critically analyses three key texts: Theniyan’s Odukkappattavargal (The Oppressed), K. Daniel’s Kaamal (Mirage) and S. Ganesalingam’s Neenda Payanam (The Long Journey). These texts reveal the complex realities of the lives of marginalized women; they portray their struggles and enduring resistances. While literary studies have explored caste and gender, there are few studies that focus on Panchamar women. To fill this gap, the study used intersectional theory (Kimberlé Crenshaw), postcolonial perspectives (Ania Loomba), caste–gender theories (Leela Dube), and gender performance theory (Judith Butler). A qualitative approach was adopted, combining close text analysis and semi-structured interviews with Panchamar community in the Jaffna region. This approach provided an opportunity to connect fiction and lived experiences. Thematic analysis revealed recurring themes of peace, resistance, resilience, and identity. Findings show that Panchamar women, while often portrayed as victims of institutional violence, also emerge as powerful agents against caste and gender oppression. While religion, tradition, and politics fail to provide complete liberation, literature and lived experiences reveal women’s continued struggle and striving for dignity and equality. The study concludes that Panchamar women, despite being portrayed as victims of caste and gender oppression, demonstrate resilience, identity affirmation, and even resistance through silence; silence appears to be a unique, powerful form of resistance.
Keywords: Caste; Intersectionality; Panchamar women; Representation; Resilience